IMPLEMENTASI PJBL DALAM PEMBELAJARAN ENGLISH FOR PHYSICS : PERSEPSI DAN PEMAHAMAN KONSEPTUAL MAHASISWA - Nusa, Jeilen Gabriela Nikita; Marcellino Christofel Mambu; Ishak Pawarangan; Jeane Verra Tumangkeng (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
This study aimed to analyze student perceptions and the impact of Project-Based Learning (PjBL) integrated with English for Physics (EFP) on students' conceptual understanding in the Physics Laboratory II course. Addressing previous research gaps that focused separately on physics concept understanding or EFP instruction without involving laboratory experiments, this study involved 10 physics students from Universitas Negeri Manado. Data were collected through perception questionnaires and post-test conceptual understanding tests, then analyzed to evaluate the effectiveness of this approach. The results indicated that PjBL significantly enhanced students' conceptual understanding, with the class's average post-test score reached 83.00. PjBL's contribution to conceptual understanding was particularly high in